The Effect Of Product Quality On Purchasing Decisions - Rita Zahara (Dinasti International Journal of Education Management And Social Science, 2024)
In this study there are two variables, namely variable X (Product Quality) and variable Y (Purchase Decision). This research was conducted to determine the Product Quality at PT. X, Purchase Decision at PT. X, and the effect of product quality on purchasing decisions at PT. X. The methods used in this research are descriptive methods and verification methods. The data used are primary and secondary data generated through observation, interviews, questionnaires (questionnaires) and literature. Sampling was done with purposive sampling technique. The hypothesis of this study is that there is an effect of product quality on purchasing decisions at PT. X. To measure the influence of these variables, the classical assumption test, simple linear regression, and the coefficient of determination are used with the help of the software application system (SPSS). Based on the results of data analysis using statistical methods, the results of the classical assumption test are valid and reliable, the results of the correlation coefficient are included in the strong category, and the coefficient of determination (KD) is large. Based on these results it can be concluded that product quality has a positive and significant effect on purchasing decisions at PT. X.